The aspartyl protease TgASP5 mediates the export of the Toxoplasma GRA16 and GRA24 effectors into host cells. (6th September 2015) - Curt‐Varesano, Aurélie; Braun, Laurence; Ranquet, Caroline; Hakimi, Mohamed‐Ali; Bougdour, Alexandre
Summary: Toxoplasma gondii and Plasmodium species are obligatory intracellular parasites that export proteins into the infected cells in order to interfere with host‐signalling pathways, acquire nutrients or evade host defense mechanisms. With regard to export mechanism, a wealth of information in Plasmodium spp. is available, while the mechanisms operating in T .  gondii remain uncertain. The recent discovery of exported proteins in T .  gondii, mainly represented by dense granule resident proteins, might explain this discrepancy and offers a unique opportunity to study the export mechanism in T .  gondii . Here, we report that GRA16 export is mediated by two protein elements present in its N‐terminal region. Because the first element contains a putative Plasmodium export element linear motif (RRLAE), we hypothesized that GRA16 export depended on a maturation process involving protein cleavage. Using both N‐ and C‐terminal epitope tags, we provide evidence for protein proteolysis occurring in the N‐terminus of GRA16. We show that TgASP5, the T .  gondii homolog of Plasmodium plasmepsin V, is essential for GRA16 export and is directly responsible for its maturation in a Plasmodium export element‐dependent manner. Interestingly, TgASP5 is also involved in GRA24 export, although the GRA24 maturation mechanism is TgASP5‐independent. Our data reveal different modus operandi for protein export, in which TgASP5 should play multiple functions. Abstract : How Toxoplasma gondii effector proteins are exported to the host cell is currently unknown. In the light of the mechanism described in Plasmodium, we found that the peptidase TgASP5, the Toxoplasma homolog of the Plasmepsin V, is essential for GRA16 maturation at the PEXEL motif and subsequent export in the host cell nucleus. Interestingly, TgASP5 is required for GRA24 export while maturation of the latter is independent of TgASP5, suggesting that TgASP5 plays an indirect function on GRA24 export and that a still unidentified protease is required for GRA24 maturation.